2022
DOI: 10.5194/egusphere-egu22-3643
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Groundwater Quality Assessment Using CCME WQI and GIS Technique for Ujjain City, India

Abstract: <p>Groundwater is a significant source of freshwater for people all around the world. About 97.2 % of the water on Earth is saline, with only 2.8 % available for usage as fresh water, of which approximately 20 % is groundwater. In India, a large portion of the populace relies on groundwater for drinking. The determination of water quality in residential, commercial, and industrialised areas is of great importance, and for this, the water quality index (WQI) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The Kappa coefficient measures how much less error is produced by a classification procedure when compared to an entirely random classification. [82,83,84,85] indicated that a kappa value of < 40% is poor, 40%-55% is fair, 55%-70% is good, 70%-85% very good, and >85% excellent. Therefore, a confusion matrix has been computed to obtain the kappa index.…”
Section: Accuracy Assessmentmentioning
confidence: 99%
“…The Kappa coefficient measures how much less error is produced by a classification procedure when compared to an entirely random classification. [82,83,84,85] indicated that a kappa value of < 40% is poor, 40%-55% is fair, 55%-70% is good, 70%-85% very good, and >85% excellent. Therefore, a confusion matrix has been computed to obtain the kappa index.…”
Section: Accuracy Assessmentmentioning
confidence: 99%